Performance of Waqf Fund Efficiency Managed by Zakat Institutions in Indonesia - Fatimah Iskandar Putri (SMART Insight, 2022)
Waqf has an important role not only in terms of spirituality but also from a social aspect. This study aims to measure the efficiency of waqf funds managed by zakat institutions in Indonesia using the Data Envelopment Analysis (DEA) method with a research period of 2013-2021. The research object used is fifteen zakat institutions that manage waqf funds in Indonesia. The data for this study comes from the annual financial reports of each institution for the 2013-2021 period. The input variables in this study are operating expenses and assets. And for the output variable is the collection and distribution of waqf funds. The results of this study found that the efficiency of waqf management has fluctuated from year to year and tends to increase, and the highest increase in management efficiency by institutions occurs in 2020 to 2021. Based on potential improvements, the highest inefficiencies come from distribution and collection with output-oriented analysis. Meanwhile, based on the orientation of inputs, assets and operating expenses, it also causes inefficiencies in the management of waqf funds.